2010
DOI: 10.1002/app.32688
|View full text |Cite
|
Sign up to set email alerts
|

Study on the properties of magnetorheological gel based on polyurethane

Abstract: Magnetorheological gels (MRGs) known as a new kind of magnetorheological material are composite gels containing magnetic particles suspended in polymer gels. In this study, a category of MR polymer gels based on polyurethane (PU) were prepared. The microstructures of these MRGs were observed with a digital microscope. Their rheological properties under both steady shear and oscillation testing were characterized by using a MR rheometer. The viscosity of the PU MRG decreased with the increment of NCO/OH ratio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 23 publications
0
53
0
Order By: Relevance
“…11 that partial substitution of the CIPs with as-synthesized flower-like CIPs has almost no influence on the LVE range of the dimorphic MRGs. Meanwhile, it is confirmed that the magnetic field strength also has no influence on the LVE range of MRGs [37]. As a result, the LVE range of the prepared dimorphic MRGs can be identified as 0%-0.1%.…”
Section: Dynamic Properties Under Oscillatory Shear Rheometrymentioning
confidence: 75%
“…11 that partial substitution of the CIPs with as-synthesized flower-like CIPs has almost no influence on the LVE range of the dimorphic MRGs. Meanwhile, it is confirmed that the magnetic field strength also has no influence on the LVE range of MRGs [37]. As a result, the LVE range of the prepared dimorphic MRGs can be identified as 0%-0.1%.…”
Section: Dynamic Properties Under Oscillatory Shear Rheometrymentioning
confidence: 75%
“…Similarly, the MRG has also been prepared by introducing high boiling point solvents to the high cross-linked PU matrix. The dynamic and static yield shear stress is controllable by adjusting the swollen ratio of the PU matrix [66]. Very recently, it has been found that when the swollen solvent exceeds to a critical point (~25 wt%), the final MR gel becomes unstable and the sedimentation appears under a relatively long time (3 months) [67].…”
Section: Magnetorheological Plastomersmentioning
confidence: 99%
“…This work provides a new method to control the mechanical properties of soft materials. Solvent-swollen polymer matrix has also been considered as an important candidate to improve the MR performances [62][63][64][65][66][67]. By adjusting the ratio of high boiling point diluents to reactants in the mixing polyurethane-silicone polymer gels, the MR materials can be altered from a liquid state to a solid state [62].…”
Section: Magnetorheological Plastomersmentioning
confidence: 99%
“…These famous MR fluids are normally composed of ferromagnetic or ferrimagnetic, magnetically nonlinear particles including iron, nickel, cobalt and ceramic ferrites dispersed in organic or aqueous liquids. Among these, a soft magnetic material, carbonyl iron (CI), which is a type of highly pure iron prepared by the chemical decomposition of purified iron pentacarbonyl originally developed by BASF, and its composites have attracted considerable attention because of their excellent MR characteristics with their less magnetic hysteresis and high magnetization saturation value [39][40][41][42][43][44][45][46][47][48][49][50][51][52]. When exposed to an external magnetic field, the induced dipole-dipole interaction between adjacent particles will cause the particles to align along the direction of the magnetic field, forming a series of structured chains.…”
Section: Introductionmentioning
confidence: 99%